The Effect of Safety Management Systems on Compliance with Occupational Health and Safety Protocols Among Construction Workers - Alfina, Hasni Riyas; Sembiring, Desiran; Murtiadi, Suryawan (ASTONJADRO, 2026)
In construction project management, creating a supportive work environment through adequate facilities, safe working conditions, and two-way communication between superiors and subordinates is a primary objective. This study aims to analyze the influence of safety culture on workers’ compliance with safety signage, as well as the impact of the Occupational Safety and Health Management System (SMK3) on adherence to OHS protocols and project performance in the Nuansa Cilangkap Flats construction project, East Jakarta. The research adopts an explanatory method with a quantitative approach, hypothesis testing, and fishbone diagram analysis. The independent variables include SMK3/regulations, top management commitment, OHS rules and procedures, communication, worker competence, worker involvement, and the work environment, while the dependent variable is project performance. Findings indicate that project performance is influenced by these factors, collectively contributing 55.4% (R² = 0.554). Internal factors such as awareness of PPE usage and education level, along with external factors such as the enforcement of sanctions, further strengthen OHS implementation. The study also reveals that SMK3 has been implemented in accordance with Government Regulation No. 50 of 2012, achieving a 93.5% “satisfactory” rating, although further improvements are needed to achieve optimal results.